The Axiological Foundations of Knowledge: A Comparison of Western and Islamic Perspectives and Their Integration in Supporting the Achievement of SDGs - Ismaiza Busti; Rusydi; Riki Saputra (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze and compare the axiological foundations of knowledge from both Western and Islamic perspectives and explore the potential for their integration in supporting the achievement of Sustainable Development Goals (SDGs). Theoretical Framework: Theoretical Framework focuses on the values underlying the development and utilization of knowledge, including ethical, goal-oriented, and beneficial aspects of human life. The main theories employed are epistemology and axiology from both perspectives, leading to a more holistic understanding of knowledge. Literature Review: Literature Review reveals significant differences between the Western approach, which tends to be more secular and rational, and the Islamic approach, which is more holistic, linking knowledge with spiritual and moral dimensions. Previous studies also emphasize the importance of integrating these perspectives to address the challenges of globalization and pluralism. Methods: This research employs a qualitative method with a comparative analysis approach. Data were collected through a literature review of both primary and secondary sources, including classical and contemporary works from Western philosophers and Islamic thinkers. The analysis compares the fundamental axiological principles of knowledge in both traditions and explores the potential for integration to enrich the understanding of knowledge. Results: Research findings show that despite fundamental differences in their views on the values of knowledge, there is potential for integration between Western rationalism and Islamic spiritual values. This integration provides a more comprehensive and applicable approach to knowledge development. Implications: Implications of this study highlight the importance of an educational framework that combines Western and Islamic perspectives to produce scholars who are not only technically proficient but also ethically and spiritually conscious. Novelty: Novelty of this research lies in its deeper understanding of the axiological foundations of knowledge through an interdisciplinary perspective and the exploration of potential integration between the two traditions to establish a more inclusive and applicable foundation of knowledge, which is highly relevant in supporting the SDGs.